Hubungan Kemitraan antara Pemerintah dan Warga dalam Relokasi Tambak Rejo Kota Semarang Tahun 2019 - Pamela Setya Miliasari; Dede Sri Kartini (PERSPEKTIF, 2022)
Tambak Rejo is one of the fishing villages located in Semarang City, Central Java, precisely located in Tanjung Mas Village and there is a process of relocation from the government for the welfare of the community. This study aims to analyze the partnership relationship between the Semarang City Government and residents in the relocation of Tambak Rejo in Semarang City in 2019. This study involves 3 actors, namely the Government, Tambak Rejo residents, and NGOs. The method used in this research is qualitative with data collection techniques in the form of literature study. The results of this study are related to the theory of partnership relations from Sulistiyani and Angga to show that the partnership relations that occurred in Tambak Rejo were not running smoothly and there were obstacles in the relocation process. However, with the various efforts made by the community, the Semarang City Government, and third parties, namely NGOs, the end has been going quite well. Each actor carries out his role and responsibility to achieve the goal to get a mutual agreement and no party feels disadvantaged.